AB0301 SARILUMAB AS MONOTHERAPY OR IN COMBINATION WITH CONVENTIONAL SYNTHETIC DMARDS IN PATIENTS WITH RHEUMATOID ARTHRITIS: 12-WEEK TREATMENT RESULTS FROM A MULTICENTER, OPEN-LABEL, PROSPECTIVE, SINGLE-ARM OBSERVATIONAL STUDY. (2nd June 2020) - Kivitz, A.; Gottenberg, J. E.; Bergman, M.; Iglesias-Rodriguez, M.; St John, G.; Qiu, C.; Van Hoogstraten, H.; Bessette, L.
Abstract : Background: Due to strict inclusion/exclusion criteria, randomized controlled trials (RCTs) may not represent the heterogeneous rheumatoid arthritis (RA) population encountered in routine clinical practice; longitudinal observational studies are needed to complement learnings from RCTs. The PROspective sarilumab (preFILled syringe/pen) multinational, obsErvational Study (PROFILE) is collecting information on treatment strategies and sarilumab usage patterns and adherence in routine clinical practice for up to 52 weeks in patients with moderate-to-severe RA. Objectives: In this planned interim analysis, we report baseline characteristics of patients prescribed sarilumab in routine clinical practice and the efficacy and safety of sarilumab after 12 weeks of treatment. Methods: Adults with RA (2010 ACR/EULAR criteria) can enroll in this multinational, open-label, single-arm, Phase 4 study if, per their treating physicians' judgment, they are to initiate treatment with sarilumab as mono- or combination (with csDMARD) therapy, in accordance with local labeling/prescribing information, ≤4 weeks prior to or ≤8 weeks after study Visit 1 (signed informed consent and disease characteristics documented); 1000 patients are planned for enrollment. Concomitant use of biologic or targeted synthetic DMARDs (b/tsDMARDs) is not permitted. Primary endpoint is change from baseline in Clinical Disease Activity Index (CDAI) score at Weeks 24 and 52. Statistical analyses are descriptive. Results: This analysis included 291 patients who reached, or discontinued before, the Week 12 visit, of whom 108 (37%) received sarilumab mono- and 183 (63%) received combination therapy. At baseline (BL), the monotherapy group had longer disease duration and a smaller proportion of b/tsDMARD-naïve patients than the combination therapy group (9.7 vs 8.7 years and 39% vs 53%). Baseline and week 12 CDAI values were available in 132 patients. Mean (SD) BL CDAI scores for the monotherapy and combination groups were 26.7 (13.1) and 27.0 (14.4). At Week 12, CDAI scores were improved by −9.1 (17.5) and −10.5 (13.9), and 37% (19/51) of patients receiving monotherapy and 48% (45/93) of those receiving combination therapy had achieved low disease activity (CDAI ≤10). Remission (CDAI ≤2.8) was achieved by 12% (6/51) of monotherapy and 20% (19/93) of combination-therapy patients. Overall, 55 (19%) discontinued sarilumab: 27 (9%) for an adverse event (AE), 19 (7%) for insufficient response, 4 (1%) for noncompliance, 5 (2%) for other reasons. Severe AEs leading to treatment discontinuation were leukopenia and neutropenia (n=1 patient), peripheral swelling (1), lung cancer (1), and fatigue (1). Ten patients (3%) had a treatment-emergent serious AE. Conclusion: In this planned interim analysis, sarilumab mono- or combination therapy resulted in improved disease outcomes, assessed by CDAI, at Week 12, an important treat-to-target time point. Safety and efficacy were consistent with Phase 3 trial findings, with no new safety signals, although interim results must be interpreted with caution. Future analyses will evaluate efficacy and safety after 24 and 52 weeks of treatment in routine clinical practice. Acknowledgments: Study funding and medical writing support (Laura George, Adelphi Communications Ltd, Macclesfield, UK) were provided by Sanofi Genzyme (Cambridge, USA) and Regeneron Pharmaceuticals, Inc. (Tarrytown, USA) in accordance with Good Publication Practice (GPP3) guidelines. Disclosure of Interests: Alan Kivitz Shareholder of: AbbVie, Amgen, Gilead, GSK, Pfizer Inc, Sanofi, Consultant of: AbbVie, Boehringer Ingelheim, , Flexion, Genzyme, Gilead, Janssen, Novartis, Pfizer Inc, Regeneron, Sanofi, SUN Pharma Advanced Research, UCB, Paid instructor for: Celgene, Genzyme, Horizon, Merck, Novartis, Pfizer, Regeneron, Sanofi, Speakers bureau: AbbVie, Celgene, Flexion, Genzyme, Horizon, Merck, Novartis, Pfizer Inc, Regeneron, Sanofi, Jacques-Eric Gottenberg Grant/research support from: Bristol-Myers Squibb, Pfizer, Roche, Consultant of: AbbVie, Bristol-Myers Squibb, Janssen, Lilly, MSD, Pfizer, Roche, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Gilead, Janssen, Lilly, MSD, Pfizer, Roche, UCB, Martin Bergman Shareholder of: Johnson & Johnson – stockholder, Consultant of: AbbVie, BMS, Celgene Corporation, Genentech, Janssen, Merck, Novartis, Pfizer, Sanofi – consultant, Speakers bureau: AbbVie, Celgene Corporation, Novartis, Pfizer, Sanofi – speakers bureau, Melitza Iglesias-Rodriguez Shareholder of: Sanofi Genzyme, Employee of: Sanofi Genzyme, Gregory St John Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc., Chunfu Qiu Shareholder of: Sanofi Genzyme, Employee of: Sanofi Genzyme, Hubert van Hoogstraten Shareholder of: Sanofi, Employee of: Sanofi, Louis Bessette Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck, Novartis, Pfizer, Roche, Sanofi, UCB Pharma, Consultant of: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck, Novartis, Pfizer, Roche, Sanofi, UCB Pharma, Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck, Novartis, Pfizer, Sanofi